JUMPA Vol.3 No.3 Okt 2016 STRATEGI STP DAN PENGARUHNYA TERHADAP KEPUTUSAN PEMBELIAN MACBOOK APPLE DI JAKARTA: STRATEGI STP DAN PENGARUHNYA TERHADAP KEPUTUSAN PEMBELIAN MACBOOK APPLE DI JAKARTA - Retno Fuji Oktaviani Universitas Budi Luhur (Sekolah Tinggi Ilmu Ekonomi Y.A.I - Jakarta - Indonesia, 2016)
This study aims to obtain empirical evidence about the influence of Strategy Segmenting, Targeting, and Positioning Against Buying Decision. The respondents consisted of the brand Apple for Macbook consumers in Central Jakarta. Questionnaires distributed 50 questionnaires, and 50 questionnaires distributed back that can be processed as many as 50 questionnaires. processing using the test validity, reliability testing, testing assumptions of classical, simultaneous test, and partial correlation test by SPSS for Windows version 21.0. Research has been conducted that strategy Segmenting, Targeting, and Positioning when tested together have a significant influence on the purchase decision is equal to 0.000 and when segmenting partially tested has a significant influence on the purchasing decisions of 0.028. Targeting has significant influence on the purchasing decisions of 0.202. Positioning has a significant influence on the purchasing decisions of 0.009. Influence Strategy Segmenting, Targeting, and Positioning for Purchase Decision amounted to 27.3 %, while the remaining 73.7 % are influenced by factors other causes. From the research it can be concluded, in the present case study variables Segmenting, Targeting and Positioning partial effect on purchase decision. Whereas in partial Segmenting and Positioning influence on purchasing decisions and Targeting variables did not significantly affect purchasing decisions.